Shoes Combine Painting and Patchwork Endek as A Business Opportunity - Abdini, Ni Gusti Ayu Arum; Gunawan, I Wayan; Supriyatini, Sri (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
Implementation of MBKM Entrepreneurship with Mitra Agung Bali Collection which is engaged in the fashion industryengaged in the development of weaving designs of weaving feed or endek fabrics with the characteristics of air brustechnique and surface design. In the development of surface design, Agung Bali Collection prioritizes creativity and innovation as well as art skills with gold, silver, pearl and glitter colors with massage canting techniques. During the MBKM Entrepreneurship process, the author developed a painting shoe product with a combination of patchwork. Thecombination of fabric pasting, sewing and painting techniques is intended to create an impression of aesthetic value inthe shoes chosen as a medium. The marketing that the author does is based offline and online, with promotions throughwhatsapp and Instagram. The types of research methods used are included in quantitative research and observation asdata collection methods. The results obtained were 6 shoe products combining patchwork endek with the title Roro, Gelombang Air, Daun Ginkgo, Sudut Pandang, Paus dan Galaksi.